2018
DOI: 10.5397/cise.2018.21.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Comparison of Supervised Rehabilitation and Home-based Rehabilitation for Earlier Recovery of Shoulder Motion, Pain, and Function after Rotator Cuff Repair

Abstract: BACKGROUND: This study was undertaken to compare the outcome of supervised and home exercises with respect to range of motion (ROM), pain, and Single Assessment Numeric Evaluation (SANE). We further correlated the ROM recovery and pain reduction as well.METHODS: The study included 49 patients who underwent arthroscopic rotator cuff repair. Rehabilitation was initiated after 4 weeks of immobilization. A total of 29 patients performed supervised exercise 3 times a week. Standardized education and brochures for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…[10,11] Song et al found better SANE scores but similar range of motion and pain relief when comparing supervised and home therapy. [12] The rehabilitation began after four weeks of immobilization. The present study had a rehabilitation protocol where the exercises were begun at one week from surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Song et al found better SANE scores but similar range of motion and pain relief when comparing supervised and home therapy. [12] The rehabilitation began after four weeks of immobilization. The present study had a rehabilitation protocol where the exercises were begun at one week from surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Song et al, it was observed that supervised therapy and home therapy yielded differential outcomes in terms of SANE scores, range of motion, and pain relief. Specifically, the researchers discovered that the SANE scores were significantly higher in the supervised therapy group compared to the home therapy group [12].…”
Section: Resultsmentioning
confidence: 99%